1998
DOI: 10.1152/ajpregu.1998.274.5.r1317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of daily sodium intake and ANG II on cortical and medullary renal blood flow in conscious rats

Abstract: Implanted optical fibers and laser-Doppler flow measurement techniques were used for the sequential measurement of regional renal blood flow in conscious rats to determine the effects of an increase of daily NaCl intake on the renal cortical blood flow and blood flow to the outer and inner medulla. Cortical blood flow was increased significantly (32%) by the second day when NaCl intake was increased from 1 to 7 meq/day and was increased further (50%) on the second day after a further elevation of NaCl intake t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 14 publications
6
47
1
Order By: Relevance
“…Rats fed a high-salt diet exhibit a reduction of plasma renin activity (PRA) (22) and ANG II (19,21) and impaired responses to vasodilator stimuli that are similar to those in SS rats in the present study. In a similar fashion, SS rats exhibit significantly lower PRA than SS.13 BN rats (8) and congenic rats having the Dahl R renin BN rats, and BN rats.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Rats fed a high-salt diet exhibit a reduction of plasma renin activity (PRA) (22) and ANG II (19,21) and impaired responses to vasodilator stimuli that are similar to those in SS rats in the present study. In a similar fashion, SS rats exhibit significantly lower PRA than SS.13 BN rats (8) and congenic rats having the Dahl R renin BN rats, and BN rats.…”
Section: Discussionsupporting
confidence: 70%
“…Other studies (31,32,34,48) have shown that high-salt diet alone leads to impaired vasodilation in arterioles and resistance arteries of Sprague-Dawley rats, in the absence of a change in blood pressure. Impairment of vascular relaxation in response to vasodilator stimuli during exposure to high-salt diet appears to be caused by the suppression of circulating levels of angiotensin II (ANG II) that occurs in response to elevated dietary salt intake (19,21). The latter hypothesis is supported by recent findings that continuous intravenous infusion of a low dose of ANG II to prevent ANG II suppression with high-salt diet restores the dilation in response to acetylcholine (ACh) and hypoxia that is eliminated with high-salt diet in middle cerebral arteries (MCA) (34).…”
mentioning
confidence: 99%
“…NO is also an important modulator of the vasoconstrictor influence of AngII in the renal cortical circulation (26,42). Furthermore, changes in renal cortical blood flow appear to play an important role in the chronic regulation of sodium excretion and BP (43). This result could be important considering that in AT 2 Ϫ/Ϫ mice the AT 1 receptor is upregulated in cortical structures (16).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in chronically instrumented Sprague-Dawley rats in our laboratory found no changes in MBF as daily sodium intake was increased from 0.4 to 4.0% (27). However, rats fed a high-sodium diet (4.0%) exhibited an increase in NOS-immunoreactive protein for all isoforms in the medullary tissue (58).…”
Section: Influence Of Medullary No Production On Blood Pressure Salt mentioning
confidence: 99%